Optimal Design of Planar Trusses Using Graph Theoretical Force Method - Kaveh, Ali; Khavaninzadeh, Neda (Periodica Polytechnica Civil Engineering, 2023)
In this paper, the purpose is to present an efficient graph method for the analysis of truss structures using the force method and compare the computational time with that of the stiffness approach. Naturally, the results of the optimization and the accuracy of calculation for both methods are identical, but the calculation time for the force method is less when the degree of static indeterminacy (DSI) is smaller than the degree of kinematic indeterminacy (DKI) of the structure. Three examples are designed, and optimization has been performed using the ECBO algorithm in MATLAB.